2017
DOI: 10.1080/17425255.2017.1391213
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomics of triazole antifungal agents: implications for safety, tolerability and efficacy

Abstract: Triazole antifungal agents are prescribed to treat invasive fungal infections in neutropenic and non-neutropenic patients. These antifungal agents are substrates and inhibitors of cytochrome P450 (CYP). Genetic polymorphisms in CYP2C9, CYP2C19 and CYP3A5 can lead to large population-specific variations in drug efficacy and safety, optimal dosing, or contribute to drug interactions associated with this class. Areas covered: This manuscript reviews the pharmacogenomics (i.e. the influence of genetics on drug dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 113 publications
0
28
0
Order By: Relevance
“…The recommended dose is 200 mg (intravenously or orally) every 8 h for 48 h, followed by 200 mg once daily as a maintenance dose applied 12–24 h after the last loading dose. Isavuconazole is mainly metabolized by the hepatic cytochrome 450 (CYP) 3A4/5 [1, 2], with polymorphisms [ CYP3A4*22 (rs35599367) and CYP3A5*3 (rs776746)] that lead to unexpected kinetic profiles, as observed for other drugs such as tacrolimus [3] (an immunosuppressive drug). To date, the pharmacokinetic-pharmacodynamic relationship has not been established for patients [4], as the only information available was obtained using rabbits [5, 6] or a murine model [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…The recommended dose is 200 mg (intravenously or orally) every 8 h for 48 h, followed by 200 mg once daily as a maintenance dose applied 12–24 h after the last loading dose. Isavuconazole is mainly metabolized by the hepatic cytochrome 450 (CYP) 3A4/5 [1, 2], with polymorphisms [ CYP3A4*22 (rs35599367) and CYP3A5*3 (rs776746)] that lead to unexpected kinetic profiles, as observed for other drugs such as tacrolimus [3] (an immunosuppressive drug). To date, the pharmacokinetic-pharmacodynamic relationship has not been established for patients [4], as the only information available was obtained using rabbits [5, 6] or a murine model [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Our study confirmed these findings, as none of the patients exposed to either triazoles or echinocandins in included studies had fulminant hepatitis or acute liver failure, yet adverse events rate was significantly higher in the groups exposed to triazoles. Additionally, all triazoles interact with cytochrome P450, especially with CYP3A4 and CYP3A5, while voriconazole interacts also with CYP2C19 [25] , and their potential to inhibit elimination of other drugs metabolized through the same enzymes is much higher than that of echinocandins [26] .Echinocandins are not metabolized through cytochromes (except micafungin in minor extent) and therefore do not influence elimination of other drugs that are oxidized at these enzymes in liver [21] .…”
Section: Discussionmentioning
confidence: 99%
“…At our knowledge, posaconazole is not very prone to pharmacogenetic variability due to its low metabolism unlike voriconazole. If voriconazole is substrate and inhibitor of many isoforms of cytochrome P450, posaconazole is an inhibitor but only a weak substrate [ 22 ]. Actually, absorption is clearly the rate-limiting step for pharmacokinetics of posaconazole oral suspension.…”
Section: Discussionmentioning
confidence: 99%